2017
DOI: 10.1039/c7dt01772c
|View full text |Cite
|
Sign up to set email alerts
|

MANOTA: a promising bifunctional chelating agent for copper-64 immunoPET

Abstract: Improved bifunctional chelating agents (BFC) are required for copper-64 radiolabelling of monoclonal antibodies (mAbs) under mild conditions to yield stable, target-specific imaging agents. Four different bifunctional chelating agents (BFC) were evaluated for Fab (Fragment antigen binding) conjugation and radiolabelling with copper-64. Two DOTA- (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) and two NOTA- (1,4,7-triazacyclononane-1,4,7-triacetic acid) derivatives bearing a p-benzyl-isothiocyanate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…The results obtained with [ 64/67 Cu­( nota )] − radiopharmaceuticals were quite encouraging, especially compared with the H 4 dota analogue, which is now recognized in nuclear medicine as an inappropriate chelator for both copper­(II) isotopes because of the low kinetic inertness of the corresponding complexes . On the other hand, H 3 nota was shown to be a promising 64 Cu chelator (few examples with 67 Cu are known considering its currently limited availability) and used in various bifunctional forms through its conjugation with biovectors . However, it is now admitted that, even if no one could predict it, the influence of the metal complexes on the biological properties is not linked only to the coordination properties of the chelates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained with [ 64/67 Cu­( nota )] − radiopharmaceuticals were quite encouraging, especially compared with the H 4 dota analogue, which is now recognized in nuclear medicine as an inappropriate chelator for both copper­(II) isotopes because of the low kinetic inertness of the corresponding complexes . On the other hand, H 3 nota was shown to be a promising 64 Cu chelator (few examples with 67 Cu are known considering its currently limited availability) and used in various bifunctional forms through its conjugation with biovectors . However, it is now admitted that, even if no one could predict it, the influence of the metal complexes on the biological properties is not linked only to the coordination properties of the chelates.…”
Section: Introductionmentioning
confidence: 99%
“…5 On the other hand, H 3 nota was shown to be a promising 64 Cu chelator (few examples with 67 Cu are known considering its currently limited availability) and used in various bifunctional forms through its conjugation with biovectors. 6 However, it is now admitted that, even if no one could predict it, the influence of the metal complexes on the biological properties is not linked only to the coordination properties of the chelates. Indeed, depending on the biological targets, it is important to have an array of complexes of different size, shape, lipophilicity, and charge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The 64 Cu-MANOTA complex was not transchelated in the presence of EDTA, indicating high stability of the complex. In vivo stability of 64 Cu-MANOTA immunoconjugate was demonstrated by low uptake from non-target organs and a high ratio of 64 Cu-MANOTA in target organs [ 187 ].…”
Section: Bifunctional Chelator Used In Radiopharmaceutical Agentsmentioning
confidence: 99%
“…Their results demonstrated that the chelator MANOTA (Methyl Amino triazacycloNOnane Triacetic Acid) was the most efficient. Their conjugation strategy was based on an isothiocyanate group and involved linkage to the free amine on the lysine residues 30.…”
Section: Molecular Imaging Componentsmentioning
confidence: 99%